2018
DOI: 10.3390/ani8110204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Supplementation with Quinoa Seed and/or Linseed on Immune Response, Productivity and Meat Quality in Merinos Derived Lambs

Abstract: Simple SummaryStressful conditions can play an important role in affecting welfare, productive performances and meat quality of lambs. The relation between nutrition and immune response has been investigated in the livestock production, particularly in dairy cattle and sheep. Due to costs related to animal feed it is useful to evaluate the proper feeding strategy supplementation for improving animal welfare and lamb meat quality. The present study aimed to evaluate the effects of supplementation with linseed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 40 publications
5
13
1
Order By: Relevance
“…For example, A Guerrero, C Sañudo, MM Campo, JL Olleta, E Muela, RMG Macedo and FAF Macedo [26] reported that a diet supplemented with 10% linseed and fattening for either 30 or 50 d could improve the fatty acid composition, productive, carcass characteristics and meat quality of cull ewes. According to R Marino, M Caroprese, G Annicchiarico, F Ciampi, MG Ciliberti, Ad Malva, A Santillo, A Sevi and M Albenzio [4], dietary linseed supplementation improved the meat tenderness and agrees with our current observations, which showed that dietary supplementation with linseed exhibited a lower shear force. The pH of muscle after slaughter is an important indicator of glycolytic activity; and was the basis for identifying potential PSE and DFD.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For example, A Guerrero, C Sañudo, MM Campo, JL Olleta, E Muela, RMG Macedo and FAF Macedo [26] reported that a diet supplemented with 10% linseed and fattening for either 30 or 50 d could improve the fatty acid composition, productive, carcass characteristics and meat quality of cull ewes. According to R Marino, M Caroprese, G Annicchiarico, F Ciampi, MG Ciliberti, Ad Malva, A Santillo, A Sevi and M Albenzio [4], dietary linseed supplementation improved the meat tenderness and agrees with our current observations, which showed that dietary supplementation with linseed exhibited a lower shear force. The pH of muscle after slaughter is an important indicator of glycolytic activity; and was the basis for identifying potential PSE and DFD.…”
Section: Resultssupporting
confidence: 91%
“…This difference in pH may account for the difference in muscle ber composition between the two groups since muscle ber type is related to the ultimate pH [28,29]. In the case of meat color, supplementation with linseed only reduced L* values, which is contrary to previous [4,30].…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Also, quinoa seeds contain important physiological functionalities, among which anti-microbial and anti-inflammatory activities. Particularly, Marino et al (2018) found that quinoa seeds supplementation can help lamb to cope with stressful events due to the close link between stress responses and the immune system and for improving meat tenderness. Under an agro-ecological perspective, another strength point is that the use of protein crops has also environmental advantages because they fix nitrogen in soils reducing the use of fertiliser.…”
Section: Strengthsmentioning
confidence: 99%
“…The capacity of the immune system is vital for health during fattening, of which the level not only affects the daily weight gain but also the disease incidence. In the last few years, several studies have investigated the strong relation between nutrition and immune response in livestock production, particularly in dairy cows [ 29 , 30 , 31 ] and sheep [ 32 , 33 ]. We measured an index of the immune system for appreciating the mixture diets with the same nutrition concentration.…”
Section: Discussionmentioning
confidence: 99%